Reports on corporate governance. - EconomicaIndia Info-Services. (New Delhi : EconomicaIndia Info-Services, 2004)
Comprises 9 documented reports; with reference to India.
"Book+CD-Rom."
Issued also on CD-ROM.
uaj 24/03/2015
Loan
Keywords: Corporate governance -- India